The formation of the methodology for the economic optimization of managerial decisions on transport - A. V. Kurbatova; E. S. Kurbatova; V. A. Persianov (Вестник университета)
The urgency of the development of transport communications and the need to optimize their work, to develop a methodology for the study of transport as a specific industry has been substantiated. The issues of emergence and evolution of methods of economic research in transport in the context of general scientific methodology at various historical stages of development of domestic and foreign science have been considered. The characteristic of views of domestic and foreign scientists and experts on formal and substantial-essential methods of research has been given. The basic principles of a systematic approach to solving complex scientific and practical problems in the fieldof transport have been outlined.